2005
DOI: 10.1158/1535-7163.mct-04-0315
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan pharmacokinetic and pharmacogenomic alterations induced by methylselenocysteine in human head and neck xenograft tumors

Abstract: The combination of methylselenocysteine and irinotecan (CPT-11) is synergistic against FaDu and A253 xenografts. Methylselenocysteine/CPT-11 increased tumor cure rate to 100% in FaDu and to 60% in A253. In this study, the effect of methylselenocysteine on pharmacokinetic and pharmacogenetic profiles of genes relevant to CPT-11 metabolic pathway was evaluated to identify possible mechanisms associated with the observed combinational synergy. Nude mice bearing tumors (FaDu and A253) were treated with methylselen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(29 reference statements)
3
7
0
Order By: Relevance
“…The results from serial biopsies indicated that clinical benefit to therapy was only observed in patients who exhibited a decrease or no induction in Drg1 protein expression. These findings are consistent with emerging data that Drg1 plays an essential role in the resistance to CPT-11 (31), and suppressing its expression both by pharmacologic or molecular means could increase sensitization to this agent both in vitro and in vivo across a spectrum of tumor types. Nevertheless, the function of this protein relative to chemotherapy resistance has remained essentially unknown.…”
Section: Discussionsupporting
confidence: 91%
“…The results from serial biopsies indicated that clinical benefit to therapy was only observed in patients who exhibited a decrease or no induction in Drg1 protein expression. These findings are consistent with emerging data that Drg1 plays an essential role in the resistance to CPT-11 (31), and suppressing its expression both by pharmacologic or molecular means could increase sensitization to this agent both in vitro and in vivo across a spectrum of tumor types. Nevertheless, the function of this protein relative to chemotherapy resistance has remained essentially unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Azrak et al [23] previously evaluated and compared the expression of multiple molecular markers in untreated controls of A253 and FaDu xenografts that were known to be associated with the irinotecan metabolic pathway. Briefly, no significant difference (p<0.05) in expression levels of those investigated markers was associated with the enhanced therapeutic efficacy of irinotecan except decreased expressions of ATP binding cassette transporters (ABCC1 and ABCG2, efflux pumps of SN-38 the active metabolite of irinotecan) and SN-38 resistant gene developmentally regulated GTP binding protein 1 (DRG1).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the protective effect of selenium against irinotecan-induced host toxicities could be due to enhanced activities of carboxylesterases/UDPGT encoded by Ugt1a and/or Cyp3a4/Cyp3a5 by selenium. Although it has been reported that selenium could significantly increase expression of Cyp3a5 [25], it is presently unknown if the expression of Cyp3a4 is elevated. Promoting expression of Ugt1a by selenium has also been reported [26, 27].…”
Section: Resultsmentioning
confidence: 99%